1989
DOI: 10.1111/j.1550-7408.1989.tb02718.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Hymenostome Affinities in an Apostome Ciliate

Abstract: The functional mouth of exuviotrophic apostome ciltates appears only after an elaborate metamorphosis that begins at the onset of the molting of their crustacean hosts. In the tomite. a non‐feeding migratory stage, a mid‐ventrai depression at the origin of kineties x, y and z has been misidentified as the cytostome. Studies of fine structure and morphogenesis identify the true but nonfunctional cytostome—the subapiral lateral canal —and the falciform and ogival fields as the adoral ciliature. The anterior row … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The tomites of these species have somatic monokinetids with an ultrastructural pattern that resembles other oligohymenophoreans. Bradbury (1989) suggested that similarities in the life cycles and the somatic ciliary ultrastructure of hymenostomes and apostomes justified a placement of the apostome ciliates as a suborder within the order Hymenostomatida. Phylogenetic analyses inferred from SSU rRNA gene sequence data supported the monophyly of apostomates and revealed sufficient genetic divergence to other subclasses to maintain this group as a separate subclass of the Oligohymenophorea (Clamp et al.…”
Section: Discussionmentioning
confidence: 99%
“…The tomites of these species have somatic monokinetids with an ultrastructural pattern that resembles other oligohymenophoreans. Bradbury (1989) suggested that similarities in the life cycles and the somatic ciliary ultrastructure of hymenostomes and apostomes justified a placement of the apostome ciliates as a suborder within the order Hymenostomatida. Phylogenetic analyses inferred from SSU rRNA gene sequence data supported the monophyly of apostomates and revealed sufficient genetic divergence to other subclasses to maintain this group as a separate subclass of the Oligohymenophorea (Clamp et al.…”
Section: Discussionmentioning
confidence: 99%
“…There are other kineties near the cytostome, but whether they are oral kineties in the sense that they aid in feeding and also lack the structure of somatic kineties remains to be determined [3]. A conspicuous kinetal fragment originates subapically, but posterior to the origin of K l .…”
Section: Resultsmentioning
confidence: 99%
“…2C, 3). The rosette-associated pore (sometimes erroneously termed the "cytostome"; see Bradbury (1989) for a discussion) is small and often not visible even after silver impregnation. When visible, it appears as a small dark circle at the posterior edge of the rosette, interrupting the ventral "hook" of somatic kineties (described below) (Fig.…”
Section: Tomitementioning
confidence: 99%